Penerapan Terapi Life Review terhadap Kemampuan Fungsi Kognitif Lansia - Nilawati; Rahmawati Ramli; Rahmat Hidayat (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Life review therapy is a modality therapy by remembering past events that can be used to improve cognitive function abilities experienced by the elderly. This study aims to determine the effect of life review therapy on the cognitive functioning abilities of the elderly in the Padangloang village area, Bulukumba Regency. This study used a pre-experimental research design with a one-group pre-test and post-test design approach. Sampling in this study used purposive sampling with a sample size of 69 respondents. The data collection instrument in this study was the measurement of cognitive function using the MMSE and standard operating procedures for life review therapy. The results of this study indicate that based on the results of the Wilcoxon signed rank test statistical test on the value of cognitive function before and after being given life review therapy, it obtained a significant value p = 0.000 <0.05, meaning that there was a significant effect between life review therapy on the cognitive function of the elderly. So it can be concluded that in this study there was an effect of life review therapy on the cognitive functioning abilities of the elderly in the Padangloang village area, Bulukumba Regency.